MM-398 Achieves Primary Endpoint of Overall Survival in Phase III Study in Patients with Gemcitabine Refractory Metastatic Pancreatic Cancer - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Tufts Medical Center Teddy Bear (Formerly F.A.O. Schwartz Teddy Bear). Boston, MA, USA.